Making the Invisible of Learning Visible: Pre-service Teachers Identify Connections between the Use of Literacy Strategies and their Content Area Assessment Practices - Mitton-Kukner, Jennifer; Murray Orr, Anne (Alberta Journal of Educational Research, 2015)
In this paper we describe four ways secondary pre-service teachers appeared to be developing assessment practices during field experience, after taking a content area literacy course. This paper arises from a multi-year study exploring pre-service and beginning content area teachers’ use of literacy strategies in teaching mathematics, science, and other content areas. Pre-service teachers’ descriptions of their teaching revealed how they understood assessment and literacy practices during field experience as intertwined and symbiotic. Pre-service teachers discussed the use of literacy strategies as multi-faceted and serving multiple assessment purposes in their classrooms, enabling them to better understand student learning by making the invisible processes of thinking visible. Dans cet article, nous décrivons quatre façons dont les enseignants en formation semblaient développer des pratiques d’évaluation pendant une expérience sur le terrain et après avoir suivi un cours en alphabétisation aux contenus adaptés. Les résultats découlent d’une étude pluriannuelle portant sur l’emploi de stratégies en alphabétisation par des enseignants en formation et des enseignants débutants offrant des cours de maths, de sciences et d’autres disciplines. Les descriptions par les enseignants en formation de leur enseignement ont révélé que pendant l’expérience sur le terrain, ils ont compris le lien serré et symbiotique entre l’évaluation et les pratiques en alphabétisation. Les enseignants en formation ont également décrit leurs stratégies en matière d’alphabétisation comme étant multidimensionnelles et aptes à satisfaire à plusieurs objectifs d’évaluation dans leurs classes, ce qui rendait visibles les processus invisibles de réflexion et leur permettait ainsi de mieux comprendre l’apprentissage par leurs élèves.